The Relevance of Personal Selling in Today's Marketing Scenario-A Theoretical Perspective - Markose, Binu; Jayachandran, S. (Indian Journal of Marketing, 2009)
Personal selling is one of the oldest forms of promotion. Promotion, as part of the marketing mix, increases company sales by communicating product information to potential customers. The four basic parts of a firm's promotional effort are personal selling, advertising, public relations, and sales promotion. Personal selling can be defined as personal communication of information to persuade a prospective customer to buy something-a good, service, idea, or whatever-that satisfies an individual's needs. It is the personal selling process that allows marketers the greatest freedom to adjust a message to satisfy customers' information needs. Personal selling allows the marketer or seller to communicate directly with the prospect or customer and listen to his or her concerns, answer specific questions, provide additional information, inform, persuade, and possibly even recommend other products or services.